Tracking neurocognitive performance following concussion in high school athletes - Covassin, T.; Elbin, R. J.; Nakayama, Y. (The Physician and Sportsmedicine, 2010)
Objective To extend previous research designs and examine cognitive performance up to 30 days postconcussion. Method A prospective cohort design was used to examine 2000 athletes from 8 mid-Michigan area high schools to compare baseline neurocognitive performance with postconcussion neurocognitive performance. All concussed athletes were readministered the Immediate Post Assessment and Cognitive Test (ImPACT) at 2, 7, 14, 21, and 30 days postconcussion. Results A total of 72 high school athletes (aged 15.8 ± 1.34 years) sustained a concussion. A significant within-subjects effect for reaction time (F = 10.01; P = 0.000), verbal memory (F = 3.05; P = 0.012), motor processing speed (F = 18.51; P = 0.000), and total symptoms following an injury (F = 16.45; P = 0.000) was found. Concussed athletes demonstrated a significant decrease in reaction time up to 14 days postconcussion (P = 0.001) compared with baseline reaction time. Reaction time returned to baseline levels at 21 days postinjury (P = 0.25). At 7 days postinjury, impairments in verbal memory (P = 0.003) and motor processing speed (P = 0.000) were documented and returned to baseline levels by 14 days postinjury. Concussed athletes self-reported significantly more symptoms at 2 days postconcussion (P = 0.000) and exhibited a resolution of symptoms by 7 days postinjury (P = 0.06). Conclusion High school athletes could take up to 21 days to return to baseline levels for reaction time. These data support current recommendations for the conservative management of concussion in the high school athlete.